2017
DOI: 10.1371/journal.pone.0174210
|View full text |Cite
|
Sign up to set email alerts
|

Norms and stigma regarding pregnancy decisions during an unintended pregnancy: Development and predictors of scales among young women in the U.S. South

Abstract: BackgroundNorms and stigma regarding pregnancy decisions (parenting, adoption, and abortion) are salient to maternal well-being, particularly for groups disproportionately affected by unintended pregnancy. However, there are few validated measures of individual-level perceptions of norms and stigma around pregnancy decisions. Additionally, little is known about variation in the content of norms regarding pregnancy decisions, and in stigma related to violations of these norms, across socio-demographic groups.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Abortion stigma is one of a broader range of reproductive stigmas that affects most people seeking abortion [1,2]. A national study of over 4,000 U.S. abortion patients indicated that nearly two-thirds reported that people would look down on them if they knew they had an abortion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Abortion stigma is one of a broader range of reproductive stigmas that affects most people seeking abortion [1,2]. A national study of over 4,000 U.S. abortion patients indicated that nearly two-thirds reported that people would look down on them if they knew they had an abortion [3].…”
Section: Introductionmentioning
confidence: 99%
“…While the aforementioned studies have explored social norms or stigmas regarding several sexual and reproductive health behaviors, to our knowledge, no recent U.S. studies have explored social norms and stigma concerning unintended pregnancy as related to use of dual contraceptive methods among young adult women. Social norms and stigma involving unintended pregnancy are closely tied to social expectations and sanctions for the circumstances by which women have unintended pregnancies, including uncommitted sexual relationships and financial instability, behavior that results in unintended pregnancy, such as sexual activity and contraceptive failure, and motherhood (Smith et al 2016, Rice et al 2017. Women may be motivated to use contraceptive methods to avoid any or all of the intersecting stigmas that women who have an unintended pregnancy face.…”
Section: Introductionmentioning
confidence: 99%
“…This study has limitations. First, women’s reports about their preferences for abortion or adoption may be underreported due to stigma [ 18 , 19 ]. We note, however, that more than 30% of women disclosed they had considered abortion during this pregnancy, indicating that our study procedures did encourage women to disclose.…”
Section: Discussionmentioning
confidence: 99%